Development and application of an inflation-based productivity model (2007)
The paper presents a productivity model with an inflation component based on an established productivity measurement theory. The motivation for writing this paper is the need for conflict resolution at the implementation of productivity incentive programs. A common complaint from trade unions and organizations is that productivity is inaccurately assessed when the traditional input-output approach is utilized. The support for this argument is that a general rise in prices of materials utilized for production activities, without corresponding added values to the materials takes away the work group productivity efforts. This does not reveal the true measure of productivity. From the results obtained, there is a significant difference between the values obtained when the traditional productivity formula is used to compute the performance of a work group compared with the formula proposed in this work. This may be a strong point and a justification for the trade union argument. The limitation of the study is the difficulty that exists in monitoring the inflation values of the multiple products utilized as inputs into the production activities. For computational activities, a factor is chosen. The novelty of the model could be traced to the fact that it is the first time that such an approach and a systematic analysis would be made through the incorporation of the inflation factor into the productivity models.